Private College Students Deserve Free Speech - Corbin Robinson (Washington University Journal of Law and Policy, 2023)
Freedom of speech is an ever-evolving legal issue facing all communities. Campus speech has been particularly prominent due to cases like Brown v. Jones County Junior College. Brown illustrates the dangers to students on campuses that lack “free speech” protections. After experiencing wrongful suppression of their speech activities, the students in Brown fortunately had a legal avenue to relief through 42 U.S.C. § 1983. However, had the same deprivation of rights occurred on a private college campus, no relief would have been available. This Note addresses the issue of suppressed speech on private school campuses and offers a proposed legislative solution for states to adopt. Using Missouri colleges as a case study, the Author demonstrates the efficacy of his proposed legislation and regulatory enforcement mechanisms. The Author provides a thorough historical background on the First Amendment, paying particular attention to its original meaning and interaction with other parts of the Constitution, like the Due Process Clause and the Fourteenth Amendment. The Author then explores the development of the academic freedom doctrine and how it has intersected with the First Amendment on college campuses. After considering various judicial and legislative options available for extending free speech rights to students attending private institutions, the Author outlines a proposal for state legislatures to enact laws which require private colleges to guarantee free speech protections for students.
Keywords: due process; free speech; private college; students; academic freedom; fourteenth amendment; missouri colleges; legislation; guarantee protections; constitutional rights; case study; campus speech; Brown; deprivation of rights; suppressed speech; evolving legal issue